KONSEP ADAB MENURUT SYED MUHAMMAD NAQUIB AL-ATTAS - Jali, Ahmad Nur; W, Undang Ruslan (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2024)
Syed Muhammad Naquib al-Attas is one of the great thinkers in Muslim history, a leading contemporary Muslim thinker in the international world, and has paid a lot of attention to the problems faced by Muslims in the modern world, especially issues of education and manners. His opinions and efforts to improve education and manners were extraordinary. The problems presented regarding education are expressed with great arguments. That is the reason researchers want to explore and study this theme. The research method used in this research is library research with a qualitative approach. The analysis used is content analysis and descriptive analysis. The results of the discussion revealed about the concept of adab, this concept can be understood and applied in any place and time. There are six concepts of adab, namely; First, socializing the goals of education as a process of instilling manners that begins with tazkiyatun nafs. Second, arrange the educational curriculum hierarchically with the classification of fardhu 'ain sciences and fardhu kifayah sciences. Third, create programs and methods based on the principles of al-taadub tsumma al-ta'allum through study, habituation, example and discipline. Fourth, optimize the role of lecturers as muaddib who care and become role models. Fifth, formulate an education evaluation system based on etiquette and science. Sixth, prepare quality supporting facilities and infrastructure. The implications of this research include 1) character formation and educational ethics, 2) relevance of Islamic education, 3) in-depth understanding of Islamic religion, 4) development of literature and research, 5) educational reform, 6) creation of intercultural dialogue.